2013
DOI: 10.1128/mcb.00976-12
|View full text |Cite|
|
Sign up to set email alerts
|

Fat Body dSir2 Regulates Muscle Mitochondrial Physiology and Energy Homeostasis Nonautonomously and Mimics the Autonomous Functions of dSir2 in Muscles

Abstract: Sir2 is an evolutionarily conserved NAD؉ -dependent deacetylase which has been shown to play a critical role in glucose and fat metabolism. In this study, we have perturbed Drosophila Sir2 (dSir2) expression, bidirectionally, in muscles and the fat body. We report that dSir2 plays a critical role in insulin signaling, glucose homeostasis, and mitochondrial functions. Importantly, we establish the nonautonomous functions of fat body dSir2 in regulating mitochondrial physiology and insulin signaling in muscles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Finally, dSir2-mediated regulation of these two dilps is shown to act independently of dFOXO, a forkhead box-O transcription factor. Transcript levels of dilp2 and dilp5 were up-regulated in flies expressing both dSir2 RNAi and dFOXO-TM (constitutively active dFOXO) constructs in their fat body similar to the levels observed in dSir2 RNAi flies (Banerjee et al, 2013). …”
Section: Nutrient Temporal and Spatial Regulation Of Dilp Expressiosupporting
confidence: 61%
See 1 more Smart Citation
“…Finally, dSir2-mediated regulation of these two dilps is shown to act independently of dFOXO, a forkhead box-O transcription factor. Transcript levels of dilp2 and dilp5 were up-regulated in flies expressing both dSir2 RNAi and dFOXO-TM (constitutively active dFOXO) constructs in their fat body similar to the levels observed in dSir2 RNAi flies (Banerjee et al, 2013). …”
Section: Nutrient Temporal and Spatial Regulation Of Dilp Expressiosupporting
confidence: 61%
“…A recent study demonstrated a role of dSir2, the Drosophila homolog of mammalian histone deacetylase SIRT1 in regulating the expression of dilp2 and dilp5 where systemic knockdown of dSir2 up-regulates those two dilps (Banerjee et al, 2012). In addition, fat body-specific knockdown of dSir2 is sufficient to up-regulate dilp2 and dilp5 expression with changes in dilp3 transcript levels in those flies not reported (Banerjee et al, 2012, 2013). Finally, dSir2-mediated regulation of these two dilps is shown to act independently of dFOXO, a forkhead box-O transcription factor.…”
Section: Nutrient Temporal and Spatial Regulation Of Dilp Expressiomentioning
confidence: 91%
“…SIRT1 is a key factor that regulates insulin sensitivity across species, including via AKT deacetylation (Banerjee et al, 2013; Liang et al, 2009; Sundaresan et al, 2011). Assaying for SIRT1-AKT interactions revealed that AKT was efficiently pulled down with SIRT1-FL and to a lesser extent with SIRT1-ΔE2 (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…Although the fruit fly brain does not seem to readily release ILPs in the presence of glucose (Geminard et al, 2009), some electrical properties of ILP-producing cells change in the presence of glucose, further suggesting a link between ILPs and carbohydrate availability (Fridell et al, 2009; Kreneisz et al, 2010). Other studies demonstrate a link with fat availability and mobilization (Banerjee et al, 2012, 2013). Although much remains to be learned about the precise regulation of insect metabolism by the ISP, it seems that this pathway is not only linked with amino acid availability, but also with fat and sugar availability, which would correspond with its presumed role of nutrient sensor.…”
Section: The Insect's Nutritional Statusmentioning
confidence: 85%